Residential Satisfaction and Behavioral Intentions among Condominium Residents in Phnom Penh, Cambodia: A Quantitative Study - Chamnab Voeun; Sarom Mok; Bora Khath; Somuny Som (Journal of Law and Social Politics, 2026)
Background: Landed housing has not been displaced by condominiums, as landed houses remain the primary dwelling choice for many Cambodian buyers. However, condominiums are increasingly used as urban residences near business centers, institutions, and employment areas, especially in Phnom Penh. Objective: This quantitative study aims to examine residents’ satisfaction and behavioral intentions toward real estate developers by identifying the key factors that influence residential satisfaction and their importance in shaping residents’ behavioral intentions. Methods: The study involved 250 condominium residents in Phnom Penh selected using convenience sampling. Data were collected through a structured questionnaire and analyzed using descriptive and inferential statistics with SPSS. Factor analysis was used to identify the underlying structure of residential satisfaction, while regression analysis was applied to examine the relationships between each set of variables and residents’ overall perceptions of satisfaction and behavioral intentions. Results: The findings show that condo characteristics, neighborhood, view and landscape, and property management are the main factors influencing residents’ overall satisfaction. Meanwhile, condo characteristics, property management, transportation, and public facilities are the main factors influencing residents’ behavioral intentions toward real estate developers. Conclusion: The study provides strategic insights for improving Phnom Penh’s condominium market and offers useful information for policymakers in developing condo-related policies and regulations. The findings are also beneficial for condo buyers, property investors, and relevant stakeholders in creating more satisfying living environments for residents.